THE CONCEPT OF ASSOCIATIVE PORTRAIT IN LINGUISTICS AND ITS LINGUISTIC DESCRIPTION - Murodova Hafiza Muhammadjonovna (Modern American Journals, 2025)
This article analyzes the essence of the concept of associative portrait, the process of its formation and linguistic description, which is one of the new directions in linguistics, on a scientific basis. The study extensively covers the realization of the emotional image of an object in the human mind through associations in the language, the psychological and linguistic aspects of the associative portrait, and the connection of this concept with national thinking. The author interprets the associative portrait as a set of associations formed in the minds of language speakers in relation to a specific object. On this basis, the associative portrait is interpreted as a linguistic phenomenon that expresses a person's knowledge, imagination and emotional relations about the object, and reflects stereotypes formed in society and national-cultural values. The article also examines the role of trigger words in the formation of an associative portrait, the analysis of the responses of the test subjects, and through them the social views formed towards mothers in Uzbek society are revealed. The results of the study show that the analysis of the associative portrait is an effective tool in studying human thinking, national identity, cultural values, and social consciousness.
Keywords: Associative portrait, linguistic association, national thinking, linguistic psychology, trigger word, cultural stereotype